Crinoidea and Holothuroidea (Echinodermata) of the abyssal Angola Basin—Results of the DIVA-1 expedition of FS "Meteor" (Cruise M48/1) - Bohn, J. M. (Zootaxa, 2006)
Agassiz trawl and epibenthic sledge samples taken at abyssal depths in the Angola Basin (southeastern Atlantic Ocean) during the expedition DIVA-1 with FS "Meteor" in July 2000 yielded a rich variety of Echinodermata: inter alia one stalked crinoid (Bathycrinus cf. aldrichianus Wyville Thomson, 1876) and altogether nine holothurian species, two of which are subspecies. One of these, Achlyonice longicornis spec. nov., is new to science, while all others have been described earlier: Deima validum validum Théel, 1879, Psychropotes semperiana Théel, 1882, Peniagone purpurea (Théel, 1882), Molpadiodemas atlanticus (R. Perrier, 1898), Molpadia liska Pawson, 1977, Protankyra brychia (Verrill, 1885), Siniotrochus myriodontus Gage & Billett, 1986 and Neolepidotrochus parvidiscus angolensis Bohn, 2005. All species collected are described and their known distributions are given. Finally, two crinoids and 21 holothurian species, so far known from the abyssal Angola Basin, are listed and their zoogeographical relationships are discussed.